Genetic Defects in DNAH2 Underlie Male Infertility With Multiple Morphological Abnormalities of the Sperm Flagella in Humans and Mice - Hwang, Jae Yeon; Nawaz, Shoaib; Choi, Jungmin; Wang, Huafeng; Hussain, Shabir; Nawaz, Mehboob; Lopez-Giraldez, Francesc; Jeong, Kyungjo; Dong, Weilai; Oh, Jong-Nam; Bilguvar, Kaya; Mane, Shrikant; et al. (Frontiers in Cell and Developmental Biology, 2021)
Asthenozoospermia accounts for over 80% of primary male infertility cases. Reduced sperm motility in asthenozoospermic patients are often accompanied by teratozoospermia, or defective sperm morphology, with varying severity. Multiple morphological abnormalities of the flagella (MMAF) is one of the most severe forms of asthenoteratozoospermia, characterized by heterogeneous flagellar abnormalities. Among various genetic factors known to cause MMAF, multiple variants in the DNAH2 gene are reported to underlie MMAF in humans. However, the pathogenicity by DNAH2 mutations remains largely unknown. In this study, we identified a novel recessive variant (NM_020877:c.12720G>T;p.W4240C) in DNAH2 by whole-exome sequencing, which fully co-segregated with the infertile male members in a consanguineous Pakistani family diagnosed with asthenozoospermia. 80-90% of the sperm from the patients are morphologically abnormal, and in silico analysis models reveal that the nonsynonymous variant substitutes a residue in dynein heavy chain domain and destabilizes DNAH2. To better understand the pathogenicity of various DNAH2 variants underlying MMAF in general, we functionally characterized Dnah2-mutant mice generated by CRISPR/Cas9 genome editing. Dnah2-null males, but not females, are infertile. Dnah2-null sperm cells display absent, short, bent, coiled, and/or irregular flagella consistent with the MMAF phenotype. We found misexpression of centriolar proteins and delocalization of annulus proteins in Dnah2-null spermatids and sperm, suggesting dysregulated flagella development in spermiogenesis. Scanning and transmission electron microscopy analyses revealed that flagella ultrastructure is severely disorganized in Dnah2-null sperm. Absence of DNAH2 compromises the expression of other axonemal components such as DNAH1 and RSPH3. Our results demonstrate that DNAH2 is essential for multiple steps in sperm flagella formation and provide insights into molecular and cellular mechanisms of MMAF pathogenesis.